A primer on current status and future opportunities of clinical optoacoustic imaging - Ferdinand Knieling; Serene Lee; Vasilis Ntziachristos (npj Imaging)
Abstract Despite its introduction in the 1970’s, it is only recent technology advances that have propelled growth in clinical optoacoustic (photoacoustic) imaging over the past decade. We analytically present the broad landscape of clinical optoacoustic applications in the context of these key technology advances, the unique contrast achieved, and the tissue biomarkers resolved. We then discuss current challenges and future opportunities to address the unmet clinical needs.